2019
DOI: 10.1038/s41598-019-51272-z
|View full text |Cite
|
Sign up to set email alerts
|

Enforced expression of phosphatidylinositol 4-phosphate 5-kinase homolog alters PtdIns(4,5)P2 distribution and the localization of small G-proteins

Abstract: The generation of phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P2) by phosphatidylinositol 4-phosphate 5-kinases (PIP5Ks) is essential for many functions including control of the cytoskeleton, signal transduction, and endocytosis. Due to its presence in the plasma membrane and anionic charge, PtdIns(4,5)P2, together with phosphatidylserine, provide the inner leaflet of the plasma membrane with a negative surface charge. This negative charge helps to define the identity of the plasma membrane, as it serves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In our initial experiments, we found that Pip5kl1 robustly localizes to cilia of Xenopus MCCs (Fig 4E). Pip5kl1 is poorly characterized, but the few studies that have been performed show that while it lacks kinase activity, it regulates membrane phospholipid content by controlling the localization of other, enzymatically active PIP5Ks (Yang et al ., 2019). Interestingly, Pip5kl1 localization extended to the full length of the cilium as marked by membrane-RFP, in contrast to AK8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our initial experiments, we found that Pip5kl1 robustly localizes to cilia of Xenopus MCCs (Fig 4E). Pip5kl1 is poorly characterized, but the few studies that have been performed show that while it lacks kinase activity, it regulates membrane phospholipid content by controlling the localization of other, enzymatically active PIP5Ks (Yang et al ., 2019). Interestingly, Pip5kl1 localization extended to the full length of the cilium as marked by membrane-RFP, in contrast to AK8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The magnified image of the 111 peak (Figure 3b) shows a shift in LTO/C‐3 h due to the oxygen vacancy. Since the coating process takes place in a reducing atmosphere, which is also favorable for oxygen vacancy formation on the surface of the LTO [32,50,51] . The Raman spectra of LTO contains a set of six bands (Figure 3c) with major bands centered at 231 cm −1 (which is F 2g vibrations in TiO 6 octahedral), 341 cm −1 (F 2g vibrations in LiO 6 octahedral), 421 cm −1 (E g vibrations in LiO 4 tetrahedral), and 668 cm −1 (A 1g vibrations in TiO 6 octahedral).…”
Section: Resultsmentioning
confidence: 99%
“…Since the coating process takes place in a reducing atmosphere, which is also favorable for oxygen vacancy formation on the surface of the LTO. [32,50,51] The Raman spectra of LTO contains a set of six bands (Figure 3c) with major bands centered at 231 cm À 1 (which is F 2g vibrations in TiO 6 octahedral), 341 cm À 1 (F 2g vibrations in LiO 6 octahedral), 421 cm À 1 (E g vibrations in LiO 4 tetrahedral), and 668 cm À 1 (A 1g vibrations in TiO 6 octahedral). In comparison, the two minor bands are located at 258 cm À 1 (attributed to F 2g vibrations in TiO 6 octahedral) and 737 cm À 1 (so-called A 1g shoulder).…”
Section: Analysis Of the Surface Coatingmentioning
confidence: 99%
“…The first endothermic peak located at around 85 °C with a weight loss of 3.4% corresponds to the dehydration process of the water adsorbed at the surface of the sample. 42 By increasing the temperature to 195 °C, the second endothermic peak is closely related to the phase transformation from H 2 Ti 3 O 7 to TiO 2 (B). 40 The corresponding weight loss for this process is 8.0% (11.4-3.4%), which is very close to the theoretical value (7.0%).…”
Section: Invariant Line Calculation Processmentioning
confidence: 99%